Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/14767058.2017.1330881
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting cell-free DNA fetal fraction and the consequences for test accuracy

Abstract: The fetal fraction in maternal plasma cfDNA increased with gestational age, serum pregnancy-associated plasma protein A (PAPP-A), β-hCG, and PlGF and decreased with increasing maternal BMI. There was no significant correlation between low FF and test accuracy, when FF was above 4%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 28 publications
8
70
3
4
Order By: Relevance
“…Our study provides further evidence that increased BMI is correlated with decreased fetal fraction, as has been established in previous studies . Furthermore, other studies including that by Ashoor et al found that fetal fraction also varied depending on ethnicity, although this was not explored in our study .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our study provides further evidence that increased BMI is correlated with decreased fetal fraction, as has been established in previous studies . Furthermore, other studies including that by Ashoor et al found that fetal fraction also varied depending on ethnicity, although this was not explored in our study .…”
Section: Discussionsupporting
confidence: 87%
“…31 Our study provides further evidence that increased BMI is correlated with decreased fetal fraction, as has been established in previous studies. 13,23,26 Furthermore, other studies including that by Ashoor et al found that fetal fraction also varied depending on ethnicity, although this was not explored in our study. 13 The reported reasons for failure in our study are distributed in a similar fashion to those demonstrated previously with both Benn and Norton and their colleagues reporting that around half of the 'no results' in their studies were attributable to low fetal fraction.…”
Section: Main Findingsmentioning
confidence: 58%
See 2 more Smart Citations
“…However, cffNIPT performance highly depends on the fetal fraction (FF), defined as the proportion of fetal-derived cell-free DNA in the total cell-free DNA component found in maternal plasma. Thus, the FF must exceed 3–4% to provide a low false negative rate [2]. Several factors including body mass index (BMI) affect the FF.…”
Section: Introductionmentioning
confidence: 99%